Iatrogenic Osteomalacia and Myopathy due to Phosphate Depletion. Issue 5924 (20th July 1974) - Baker, L. R. I.; Ackrill, P.; Cattell, W. R.; Stamp, T. C. B.; Watson, L.
Abstract : In a patient receiving regular dialysis prolonged hypophosphataemia due to aluminium hydroxide therapy resulted in osteomalacia and severe proximal myopathy. Both osteomalacia and myopathy responded to correction of hypophosphataemia without vitamin D therapy.